Evaluation of the Implementation of the Physical Program of PT. Ock Athletic Club Phase I in 2024 - Supriyatnak, Kokom; Wahyudi, Johan; Dermawan S, M. Ariy (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to evaluate the Physical Program of PT.OCK Athletic Club Phase I in 2024. The evaluation method used in this research is Context Input Process Product (CIPP) obtained from a qualitative approach and a quantitative approach and explained in descriptive research.  The research results show that the basic context and objectives are clear. In terms of the input aspect of the program being implemented, human resources, infrastructure and financial sources are adequate. In the process there were significant obstacles with the training schedule, participant character in body posture, age adjustment, management and organization of the ratio of trainers and participants was not optimal, coaching, more precisely, physical training carried out during that period was aimed at finding out the NAJ results (Final Score Physical) data has been obtained. From the product data, the existing results become a benchmark for Physical Program. PT. OCK Athletic Club Phase I in 2024 to further increase the duties and responsibilities of PT. OCK Athletic Club to improve Physical Program development.